Strategies for Developing Soft Skills, Hard Skills, and Student Entrepreneurial Interest - Hamzah, Sitti Nuraisyah; Alam, Syamsu; Syam, Agus (Universitas Negeri Makassar, 2024)
This research aims to determine the strategy for developing soft skills, hard skills and entrepreneurial interests of students majoring in culinary arts at SMK Negeri 6 Makasar. The right strategy to improve students' abilities so they can have an entrepreneurial spirit at a young age and can reduce the unemployment rate among vocational school graduates. The research method used is descriptive qualitative research using data collection methods through observation, interviews and documentation of research objects which are then analyzed using SWOT analysis. Developing soft skills such as good communication, leadership, and critical thinking, along with hard skills through webinars and digital entrepreneurship training, can enhance students' interest in entrepreneurship and improve their business prospects, ultimately addressing unemployment rates among vocational school graduates.